An enquiry concerning human understanding and other writings - Hume, David, 1711-1776 (Cambridge Texts in the History of Philosophy., 2007)
David Hume's An Enquiry Concerning Human Understanding, first published in 1748, is a concise statement of Hume's central philosophical positions. It develops an account of human mental functioning which emphasizes the limits of human knowledge and the extent of our reliance on (non-rational) mental habits. It then applies that account to questions of free will and religious knowledge before closing with a defence of moderate scepticism. This volume, which presents a modified version of the definitive 1772 edition of the work, offers helpful annotation for the student reader, together with an introduction that sets this profoundly influential work in its philosophical and historical contexts. The volume also includes a selection of other works by Hume that throw light on both the circumstances of the work's genesis and its key themes and arguments.